2012
DOI: 10.1089/met.2011.0052
|View full text |Cite
|
Sign up to set email alerts
|

Serum Adipokine Levels in Type 1 Diabetic Patients: Association with Carotid Intima Media Thickness

Abstract: Increased adiponectin correlates negatively and resistin positively with CIMT in type 1 diabetic patients, but adjusting for other known predictors reveals only resistin to be associated with subclinical atherosclerosis in this group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 37 publications
4
5
1
Order By: Relevance
“…Meanwhile, significant increases in BMI, random blood sugar, HbA1c, and resistin level were observed in the diabetic children compared with the control group (p < 0.0001). This agreed with a recent study of Yazıcı et al (28) that reported higher resistin levels in type-1 diabetic patients compared with the controls, as well as many other studies (29,30). Conversely, a previous work of Schäffler et al reported lower resistin concentrations in adult patients with type-1 diabetes compared with healthy control subjects with a similar age range.…”
Section: Discussionsupporting
confidence: 92%
“…Meanwhile, significant increases in BMI, random blood sugar, HbA1c, and resistin level were observed in the diabetic children compared with the control group (p < 0.0001). This agreed with a recent study of Yazıcı et al (28) that reported higher resistin levels in type-1 diabetic patients compared with the controls, as well as many other studies (29,30). Conversely, a previous work of Schäffler et al reported lower resistin concentrations in adult patients with type-1 diabetes compared with healthy control subjects with a similar age range.…”
Section: Discussionsupporting
confidence: 92%
“…While higher leptin levels have been associated with CV events in the general population, the association of leptin with subclinical atherosclerosis is unclear. [35, 36] Our results are in agreement with another CTA study where leptin was not associated with plaque presence or extent. [37]…”
Section: Discussionsupporting
confidence: 91%
“…In the current study, resistin was significantly higher in diabetic subjects than in control subjects. Other studies have reported comparable results [17, 23]. Shalev et al .…”
Section: Discussionsupporting
confidence: 64%